Analisi Faktor-Faktor yang Mempengaruhi Keputusan Etnis Tionghoa Menggunakan Jasa Bank Syariah - Jasri, Jasri; Said, Salmah; K, Amiruddin (Institut Agama Islam Negeri Madura, 2020)
Chinese ethnic is one of the ethnic groups in Indonesia. The majority of Chinese ethnics are non-Muslim. In the midst of differences in perceptions who looked cynically following Islamic banking, most of the Chinese ethnics who are not Muslim prefer sharia banking to transact. So, this research studies the factors that influence the decision of ethnic of Chinese non-Muslim to use the services of Islamic banks. This type of research used in this research is quantitative field research thas emphasizes the aspect of objective assessment pf social phenomena where the independent variables are Environtment (X1), Psychology (X2), and Promotion (X3) and the dependent variation is the decision of ethnic of Chinese (Y). This study uses SPSS software as a tool in prosessing statistical data. The results show simultaneously three factors which were considered as significant to the decision of the ethnic of Chinese to use the services of Islamic banks. If it is related to environmental factors (X1) and Promotion (X3) influences and significantly influences ethnic of Chinese decisions, while psychology (X2) does not relate to outcome of the ethnic of Chinese agreement using the services of Islamic banks.Keywords: environment; psychology; promotion; customer decisions; ethnic Chinese